Odpowiedzi

2013-07-15T18:19:00+02:00

a)

Korzystamy ze wzoru skróconego mnożenia:

 

(a-b)^{3}=a^{3}-3a^{2}b+3ab^{2}-b^{3}\\\\(3-\sqrt{3})^{3}=3^{3}-3*3^{2}*\sqrt{3}+3*3*(\sqrt{3})^{2}-(\sqrt{3})^{3}=\\27-3*9*\sqrt{3}+9*3-3\sqrt{3}=27-27\sqrt{3}+27-3\sqrt{3}=\\54-30\sqrt{3}

 

b)

Korzystamy ze wzoru skróconego mnożenia:

 

(a+b)^{3}=a^{3}+3a^{2}b+3ab^{2}+b^{3}\\\\(1+2\sqrt{5})^{3}=1^{3}+3*1*2\sqrt{5}+3*1*(2\sqrt{5})^{2}+(2\sqrt{5})^{3}=\\1+6\sqrt{5}+3*20+40\sqrt{5}=1+6\sqrt{5}+60+40\sqrt{5}=\\61+46\sqrt{5}

 

c)

Korzystamy ze wzoru skróconego mnożenia:

 

(a-b)^{3}=a^{3}-3a^{2}b+3ab^{2}-b^{3}\\\\(\sqrt{2}-4)^{3}=(\sqrt{2})^{3}-3*(\sqrt{2})^{2}*4+3*\sqrt{2}*4^{2}-4^{3}=\\2\sqrt{2}-3*2*4+3\sqrt{2}*16-64=2\sqrt{2}-24+48\sqrt{2}-64=\\50\sqrt{2}-88

1 5 1